2019
DOI: 10.1097/pas.0000000000001396
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Gastrointestinal Neuroectodermal Tumor

Abstract: A malignant gastrointestinal neuroectodermal tumor (GNET) is rare, and it is therefore yet to be completely understood. This study aimed to present the clinicopathologic features of GNET, including treatment information. We included 19 patients with GNET with a mean tumor size of 4.2 cm. The most common site of tumor origin was the small intestine (57.9%), followed by the stomach (15.8%), colon (10.5%), ileocecal junction (5.3%), lower esophagus (5.3%), and anal canal (5.3%). Microscopically, the tumors were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 29 publications
1
54
1
Order By: Relevance
“…6 The majority of GNET patients are young adults aged 20 to 40 years. 11 Only 5 patients were over 60 years old, and 1 was under 10 years. 8,12 Distinct from the male predominance of CCS-GIT lesions, women prevailed in the GNET group, with a ratio of 1:1.5 between males and females (P < 0.01).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 The majority of GNET patients are young adults aged 20 to 40 years. 11 Only 5 patients were over 60 years old, and 1 was under 10 years. 8,12 Distinct from the male predominance of CCS-GIT lesions, women prevailed in the GNET group, with a ratio of 1:1.5 between males and females (P < 0.01).…”
Section: Discussionmentioning
confidence: 98%
“…21 Drug resistance and the lack of specific targeted treatments are the main problems of clinical treatment. 11 According to the K-M analysis, aggressive chemotherapy or radiotherapy was effective in increasing the time to death but not to first metastasis. Postoperative routine adjuvant therapy showed no effect on survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that GNET is a unique clinicopathological entity harboring EWSR1-ATF1/CREB1 fusions, and it can arise at any location in the GI tract, with the small intestine (particularly ileum) being the most common (4,6). According to published literatures, only a minority of cases originated from the upper aerodigestive tract (e.g., tongue, parapharyngeal space, and bronchia) (1, 4, 7-9), which we regard as location extension in a broad sense.…”
Section: Discussionmentioning
confidence: 99%
“…GNET is highly malignant and prone to develop local recurrence and metastasis (3,4,6). At the present, surgical resection is the mainstay of treatment for GNET, and a small number of patients have been reported to show a partial response to apatinib and anlotinib (6).…”
Section: Discussionmentioning
confidence: 99%
“…The common management was a radical excision of the tumor with wide lymphadenectomy followed by close monitoring for local recurrence and metastasis. Clinically, there were 3 patients treated with apatinib or anlotinib in these series who experienced preliminary clinical benefit (1 partial response and 1 stable disease to apatinib, 1 partial response to apatinib), indicating that apatinib and anlotinib might be reasonable options for the treatment of advanced GNET and could prolong patient survival [ 9 ]. Another study reported a case of a 30-year-old female with distal ileum GNET s/p resection and adjuvant chemotherapy with ifosfamide and epirubicin.…”
Section: Discussionmentioning
confidence: 99%